Prevalence of antibodies to the BK and JC papovaviruses in isolated populations Prevalência de anticorpos contra os papovavirus BK e JC em populações isoladas - J. A. N. Candeias; R. G. Baruzzi; S. Pripas; M. lunes (Universidade de São Paulo, 1977)
A total of 173 sera from isolated Brazilian Indian populations, 39 from the Diauarun area, and 68 from the Alto Xingú area, respectively in the North and the South of the Xingú National Park and 66 Kren-Akorore Indians, were examined for hemagglutination - inhibiting (HI) antibodies against BK and JC viruses. The global percentages of positive sera (> 1:40) were 5.2% for BK virus and 1.7% for JC virus. The distribution of positive sera according to the population groups showed one individual to be positive for BK virus in the Diauarun Indians and none of the sera contained HI antibody to JC virus; in the Alto Xingú Indians, 4 were positive for BK virus and 3 others were positive for JC virus; as regards Kren-Akorore Indians none of the sera contained antibody to JC virus, and only 4 were BK positive. Due to the limited number of observations it was neither possible to determine the time of occurrence of seroconversion nor correlate the positivity rates for both viruses in the different tribes with the respective "contact" with the white population. Foram estudados 173 soros de índios brasileiros, sendo 39 da área Diauarum, 68 do Alto Xingú e 66 índios Kren-Akorore. A pesquisa de anticorpos inibidores da hemaglutinação para os papovavirus BK e JC mostrou uma percentagem global de positividade (> 40) para os virus BK de 5,2% e para o virus JC de 1,7%. A distribuição dos soros positivos segundo sua origem foi a seguinte: dos 39 índios Diauarum somente um apresentou titulo significante para o virus BK e nenhum deles foi positivo para o virus JC; dos 68 índios do Alto Xingú, 4 apresentaram título significante para o virus BK e 3 para o virus JC, sendo estes últimos diferentes dos indivíduos positivos para o virus BK; dos 66 índios Kren-Akorore, 4 mostraram possuir título significante para o virus BK, sem positividade para o virus JC. O número reduzido de soros não permitiu estabelecer o momento da ser o conservação, em termos de idade, como não permitiu relacionar as taxas de positividade com o maior ou menor "contato" com a população branca.